The Role of School Climate in Enhancing Teacher Commitment: A Literature Reviews - Yulianti, Lili; Hadiyanto, Hadiyanto; Sulastri, Sulastri (International Journal of Educational Dynamics, 2024)
This study aims to examine the contribution of school climate to enhancing teacher commitment. A systematic literature reviews method was employed, focusing on a range of sources such as articles, books, and reports to provide a comprehensive understanding of the dynamics between school climate and teacher commitment. Key findings indicate that school climate significantly influences teacher commitment through various factors. First, effective leadership from school principals fosters a supportive and motivating environment, promoting teacher engagement and a sense of belonging. Second, positive relationships among teachers, students, and staff create a collaborative atmosphere that enhances job satisfaction and unites individuals toward common goals. Third, opportunities for professional development, such as training and workshops, enable teachers to improve their skills and remain committed to their roles. A positive school climate was also found to boost teacher well-being and job satisfaction, further solidifying their dedication to their professional responsibilities. Based on these findings, the study concludes that fostering a positive school climate is essential for enhancing teacher commitment, which directly impacts the quality of education and student academic achievement. Collaborative efforts among school leaders, teachers, and staff are crucial for creating a conducive environment that supports educational goals.